Augmented visualization cues on primary flight display facilitating pilot's monitoring performance. Issue 135 (March 2020) - Li, Wen-Chin; Horn, Andreas; Sun, Zhen; Zhang, Jingyi; Braithwaite, Graham
Highlights: The incompatible human-computer interaction in the flight deck can lead to accident/incident. Flight deck designs have to provide higher level of situation awareness by instinctively matching pilot's cognitive processes. Salient visual cues can reduce pilot's cognitive effort to eliminating the requirements of text-reading on the interface displays. The key concept behind augmented design is to merge the flight mode annunciator with raw flight data in the cockpit. Augmented visualization cues can facilitate pilots identifying the flight status quicker and more accurate compared with traditional design. Abstract: There have been many aviation accidents and incidents related to mode confusion on the flight deck. The aim of this research is to evaluate human-computer interactions on a newly designed augmented visualization Primary Flight Display (PFD) compared with the traditional design of PFD. Based on statistical analysis of 20 participants interaction with the system, there are significant differences on pilots' pupil dilation, fixation duration, fixation counts and mental demand between the traditional PFD design and augmented PFD. The results demonstrated that augmented visualisation PFD, which uses a green border around the "raw data" of airspeed, altitude or heading indications to highlight activated mode changes, can significantly enhance pilots' situation awareness and decrease perceived workload. Pilots can identify the status of flight modes more easily, rapidly and accurately compared to the traditional PFD, thus shortening the response time on cognitive information processing. This could also be the reason why fixation durations on augmented PFDs were significantly shorter than traditional PFDs. The augmented visualization in the flight deck improves pilots' situation awareness as indicated by increased fixation counts related to attention distribution. Simply highlighting the parameters on the PFD with a green border in association with relevant flight mode changes will greatly reduce pilots' perceived workload and increase situation awareness. Flight deck design must focus on methods to provide pilots with enhanced situation awareness, thus decreasing cognitive processing requirements by providing intuitive understanding in time limited situations. Graphical abstract: Image, graphical abstract